STRATEGI PENGEMBANGAN USAHA TANI KOPI ORGANIK DI KECAMATAN MEKAKAU ILIR KABUPATEN OKU SELATAN - Irawan, Senja; Sari, Fifian Permata; Okarina, Yetty (Fakultas Pertanian Universitas Mataram, 2025)
Coffee is one of the important commodities in the plantation sub-sector. Most of Indonesia's coffee production is a plantation commodity that is exported to the world market. This research was conducted in Mekakau Ilir District, South OKU Regency. Data analysis will be carried out through qualitative and quantitative descriptive analysis. Qualitative descriptive analysis is used to get an overview of organic coffee farming. While quantitative analysis uses the IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) matrices. The results of the study showed that several internal and external factors were obtained, internal factors, namely strengths; Affordable product prices, land availability, supporting human resources, sales are carried out online, good and distinctive product quality, weaknesses: Limited marketing channels, lack of infrastructure, still using simple technology, capital information, unusual tastes, lack of packaging creativity. While external factors are, opportunities: Quite large market share, increasing coffee drinking trends, digital marketing, geographical conditions and locations, market availability. While threats: Fluctuating coffee prices, coffee products from other regions, economic conditions of the lower middle class. From the research results, it can be seen that the development strategies used to develop shallot commodities in OKU Regency are SO Strategy (Improving quality, Effective marketing, Utilizing natural resources, Improving distribution networks, WO Strategy (Building cooperation with cafes and restaurants, Cooperation with the government, Developing businesses gradually, Designing attractive packaging), ST Strategy (Using flexible pricing strategies, Developing unique products, Developing affordable products), WT Strategy (Increasing production efficiency, Increasing human resource capacity, Product introduction, Increasing cost efficiency).